Larangan Menikah di Bulan Suro Pada Masyarakat Paguyuban di Desa Tulung Indah Kecamatan Sukamaju Kabupaten Luwu Utara Dalam Perspektif Hukum Islam - Ismi Andini; Helmi Kamal; Rahmawati Rahmawati (Bayt Al Hikmah: Jurnal Pendidikan dan Pengembangan Masyarakat Islam, 2025)
The urgency of this research arises from the strong belief held by the people of Tulung Indah Village regarding the prohibition of marriage during the month of Suro, which is considered a sacred month that may bring misfortune if violated. This belief persists despite lacking a clear basis in Islamic law. This study aims to explore the community’s views on the prohibition, identify the underlying factors, and examine the issue from the perspective of Islamic law. The research method employed is empirical research using a qualitative approach. Data sources consist of primary and secondary data, collected through observation, interviews, and documentation. Data validity was tested using triangulation techniques, while data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results of the study show that the majority of Tulung Indah residents still believe in and adhere to the prohibition of marriage during the month of Suro due to cultural reasons, inherited beliefs, limited religious understanding, and environmental influence. From the perspective of Islamic law, there is no evidence from the Qur’an or Hadith that forbids marriage during the month of Suro. Therefore, this tradition is not legally binding in Islamic terms. However, if the tradition leads to polytheism or contradicts Islamic creed (aqidah), it cannot be justified. The researcher recommends that religious leaders and academics play an active role in educating the community to correct misconceptions and misguided beliefs.